The role of herbaria for taxonomic and distributional studies in Characeae: examples from the Herbarium Mediterraneum Panormitanum (PAL) and the Florence Tropical Herbarium (FT) - Angelo Troia; Lia Pignotti; Teresa Napolitano; Rosario Schicchi; Riccardo Maria Baldini (Palermo University Press, 2018)
Characeae is a taxonomically critical family. Taxonomical uncertainties inevitably affect its distributional data. The role of herbarium specimens, particularly types and original material, is crucial for unravelling taxonomical ‘knots’. Moreover, wet areas have undergone dramatic reduction and modification in the last century and historical herbarium specimens may represent basic documents for the reconstruction of former distributions. Some preliminary data from two different Italian Herbaria are here presented. The Herbarium Mediterraneum Panormitanum (PAL, the standard acronym according to the Index herbariorum, http://sweetgum.nybg.org/ ih) houses four folders of Characeae exsiccata. Two of them contain Italian material, the other two extra-Italian, mostly European material. Italian material totals 88 specimens, many of them collected in Sicily in 19th Century and often reviewed by Formiggini (1908). Many of these Sicilian collection localities are today deeply modified, but as later collections are quite rare, current knowledge on many taxa still relies on those very specimens, which should be carefully reviewed. As an example, one of the few known bisexual populations of Chara canescens Loisel., reported in Sicily at Pergusa Lake (one specimen is in PAL), could not be confirmed by recent exploration of the site. The Tropical Herbarium of Florence (FT) hosts 30 specimens of Characeae (data are available online: http://herbarium.univie.ac.at/database/search. php), most of them unidentified, but important because collected between the end of 19th and the first decades of 20th century in the Horn of Africa (the east African peninsula including Ethiopia, Somalia, and Eritrea, geographical core of FT collections). Present knowledge of the charophyte flora of this area is poor, and (as stated by Langangen 2015) “a more systematic survey will undoubtly produce interesting results”. - Formiggini L. 1908. Bullettino della Società Botanica Italiana 1908: 81-86. Langangen A. 2015. Acta Musei Nationalis Pragae, ...